"We are women and men now": Intimate spaces and coping labour for Syrian women refugees in Jordan. Issue 3 (4th March 2019) - Culcasi, Karen
Abstract : War affects women from the bedroom to the battlefield, but for most women war is experienced within intimate spaces. Intimate spaces are rarely the focus of mainstream academic research or media reporting; thus women's experiences with war and displacement are often concealed. Building from literature in feminist geopolitics that helps focus our attention toward everyday and intimate geopolitics, I conducted in‐depth interviews with Syrian women refugees in Jordan in order to examine how they are coping. Of the many ways that they've learned to cope, these women asserted that earning an income and adjusting to altered gender performances and relations have been both dire and formative. Many Syrian women refugees have become income providers for the first time in their lives. Some women have become their families' sole providers, and other women are now heads of households as well. Bringing literature from feminist geography, transnational and migration studies, and critical home studies together with feminist geopolitics, I offer the ideas of coping and coping labour as a framework to examine the intimate spaces of displacement. I highlight that paid work is understudied within feminist geopolitics, but such a focus renders important insights into how gender shapes experiences of displacement and how displacement is reshaping gendered relations. In this paper, I show that in the intimate spaces of displacement women have taken on traditionally masculine practices, but while their gendered performances shift, they are simultaneously entrenched as the ideals of appropriate feminine and masculine performances are recreated. Though these multiple gendered performances are creating numerous demands and challenges for Syrian women refugees, these women are also experiencing an increased sense of strength, confidence and respect as a result of their shifting performances. Abstract : I offer the ideas of coping and coping labour as a framework to examine the intimate spaces of displacement. I highlight that paid work is understudied within feminist geopolitics, but such a focus renders important insights into how gender shapes experiences of displacement and how displacement is reshaping gendered relations. Through a study of Syrian women refugees in Jordan, I highlight that gender performances are shifting and entrenching, while also causing challenges and positive effects.